Green long-after-glow luminescence of Tb3＋ in Sr2SiO4 - 王齐 邱建备 宋志国 周大成 徐旭辉 (中国物理B：英文版, 2014)
The green long-after-glow luminescence from Tb3＋-doped Sr2SiO4 phosphors, which are synthesized by the high temperature solid state reaction in a reductive atmosphere, is observed in this paper. The results show that under ultraviolet excitation, the obtained phosphors produce an intense green-lighting-emission from the Tb3＋, and the green-lighting long- after-glow luminescence related to Tb3＋ can last half an hour after the irradiation source has been removed. Moreover, the effects of co-doping Li＋, Dy3＋, Er3＋, Gd3＋, and Yb3＋ with Tb3＋ on the decay properties and thermoluminescence properties are investigated to confirm the long-after-glow mechanism.